China Satellite Navigation Conference (CSNC) 2014 Proceedings: Volume II - Sun, Jiadong; Jiao, Wenhai; Wu, Haitao; Lu, Mingquan (Lecture Notes in Electrical Engineering,, 2014)
China Satellite Navigation Conference (CSNC) 2014 Proceedings presents selected research papers from CSNC2014, held on 21-23 May in Nanjing, China. The theme of CSNC2014 is 'BDS Application: Innovation, Integration and Sharing'. These papers discuss the technologies and applications of the Global Navigation Satellite System (GNSS), and the latest progress made in the China BeiDou System (BDS) especially. They are divided into 9 topics to match the corresponding sessions in CSNC2014, which broadly covered key topics in GNSS. Readers can learn about the BDS and keep abreast of the latest advances in GNSS techniques and applications.  SUN Jiadong is the Chief Designer of the Compass/ BDS, and the Academician of Chinese Academy of Sciences (CAS); JIAO Wenhai is a researcher at China Satellite Navigation Office; WU Haitao is a professor at Navigation Headquarters, CAS; LU Mingquan is a professor at Department of Electronic Engineering of Tsinghua University.